Depressed lattice oxygen and improved thermoelectric performance in N-type Mg3Bi2-xSbxvia La-doping. (November 2021) - Shang, H.; Zhang, J.; Gu, H.; Song, S.; Chen, C.-L.; Lee, J.-F.; Shih, K.; Ren, Z.; Ding, F.
Abstract: Excellent thermoelectric performance has been realized in trace-elements-doped n-type Mg3 Bi2- x Sb x materials, but the structural origin for such improved performance hasn't been fully studied, inhibiting this effective approach to better performance. Here we present the characterizations and analyses of the atomic and electronic structures associated with La dopants in polycrystalline Mg3·2 Bi1·5 Sb0.5 using synchrotron X-ray diffraction and X-ray absorption spectra, as well as the material's thermoelectric performance. Interstitial oxygen was observed inside the cavities of the Mg6 Bi6 hexagonal cylinders in un-doped Mg3·2 Bi1·5 Sb0.5, which may account for its semiconducting behavior, while the La can effectively depresses the interstitial oxygen, resulting in the more negative valence state of Bi from −2.20 to −3.35. Furthermore, the thermoelectric performance of La-doped Mg3·2 Bi1·5 Sb0.5 has been significantly improved due to the optimized carrier concentration and the increased Hall mobility, exhibiting a zT value of ∼0.75 at 525 K. Graphical abstract: Image 1 Highlights: The atomic and electronic structures of La-doped Mg3.2 Bi1.5 Sb0.5 were analyzed. Synchrotron X-ray diffraction and X-ray absorption spectra were used. Elemental La can effectively depresses the interstitial oxygen existed in Mg3.2 Bi1.5 Sb0.5 . La-doped Mg3.2 Bi1.5 Sb0.5 showed the enhanced zT values.